2015
DOI: 10.1038/srep09948
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-stabilized superconductive yttrium hydrides

Abstract: The search for high-temperature superconductors has been focused on compounds containing a large fraction of hydrogen, such as SiH4(H2)2, CaH6 and KH6. Through a systematic investigation of yttrium hydrides at different hydrogen contents using an structure prediction method based on the particle swarm optimization algorithm, we have predicted two new yttrium hydrides (YH4 andYH6), which are stable above 110 GPa. Three types of hydrogen species with increased H contents were found, monatomic H in YH3, monatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
267
5
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 318 publications
(292 citation statements)
references
References 45 publications
18
267
5
2
Order By: Relevance
“…The compound was predicted to be superconducting with a maximum T c is 40 K near 18 GPa (μ* = 0.1) (16). Another theoretical study suggested two energetically competing hydrogen-rich polymorphs YH 4 and YH 6 (30). At 120 GPa, both are predicted to be superconductors with maximum T c of 95 K and 264 K for YH 4 and YH 6 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound was predicted to be superconducting with a maximum T c is 40 K near 18 GPa (μ* = 0.1) (16). Another theoretical study suggested two energetically competing hydrogen-rich polymorphs YH 4 and YH 6 (30). At 120 GPa, both are predicted to be superconductors with maximum T c of 95 K and 264 K for YH 4 and YH 6 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To date, simple hydrides with the highest predicted superconducting T c s are MgH 6 (271 K at 300 GPa) (29), CaH 6 (235 K at 150 GPa) (17), and YH 6 (264 K at 120 GPa) (30). In searching for other high-T c superconducting hydrides, here we investigated theoretically possible high-pressure crystal structures of La-H and Y-H. We predict the existence of new stable hydride phases of these elements, with remarkably high T c s at attainable pressures.…”
mentioning
confidence: 99%
“…Calculations have predicted that hydrogenic sodalite-like lattices will also be found in MgH 6 around 260 GPa [34] and YH 6 at 120 GPa [61].…”
Section: How To Metallize With An Electropositive Elementmentioning
confidence: 99%
“…CALYPSO has been used to investigate a great variety of materials at high pressures [33][34][35][36][37][38]. Detailed information on the calculations is provided in the Supplemental Material [39].…”
mentioning
confidence: 99%